A moderated mediation model of the relationship between Indian elementary school teachers' autonomy and perceived ease of ICT use - Arnab Kundu; Tripti Bej (Future in Educational Research)
Abstract In the 21st century, Information and Communication Technology (ICT) is a critical component of innovative teaching and learning. This study looked at the impact of teachers' autonomy on their perceived ease of using ICT and the intricate relationship between the two, involving their self‐efficacy, job satisfaction, and perceived incentives to change. Using a descriptive survey approach, 311 (134 female) Indian elementary school teachers participated in the study and provided self‐reported data. A structural equation model was employed to test the mediating roles of self‐efficacy and job satisfaction, and the moderation of perceived incentives. The results affirmed that teacher autonomy had a direct and moderately positive effect on their perceived ease of ICT use. Self‐efficacy and job satisfaction significantly and partially mediated the indirect relationships between autonomy and ease of ICT use. In the three relationship paths the perceived incentive to change had a significantly positive moderation to catalyze the relationships. Considering Indian elementary school teachers' glaring lack of autonomy, this paper suggests a policy shift involving greater teacher autonomy and the use of incentives for improved efficacy, job satisfaction, and ICT use. The relationship matrix will serve as a reference for researchers and practitioners to gain a deeper understanding of the role of teacher autonomy in addressing the global issue of limited adoption and integration of ICT by school teachers.